PENGARUH RASIO KEUANGAN TERHADAP TINGKAT KINERJA PADA BANK PEMBANGUNAN DAERAH - Mulatsih Mulatsih (ETIKONOMI, 2014)
The aim of this research is to analyze the effect of financial ratios on profitability at regional development banks. The method analysis that used in this research is multiple regressions with six variabel independent such as capital adequacy ratio, net interest margin, BOPO, loan to deposit ratio, non-performing loan, and return on equity, and the dependent variables is return on asset. The result shown that capital adequacy ratio, net interest margin, and ROE have a positive influence on ROA. BOPO and non-perfoming loan had a negative influence to return on asset. The value of R square shown that all the independent variables can explained the model with 83,7%, and the rest is about 16,7% was explained by other variables outside the model.DOI: 10.15408/etk.v13i2.1884